2017
DOI: 10.3847/2041-8213/aa8fc7
|View full text |Cite
|
Sign up to set email alerts
|

The Electromagnetic Counterpart of the Binary Neutron Star Merger LIGO/Virgo GW170817. II. UV, Optical, and Near-infrared Light Curves and Comparison to Kilonova Models

Abstract: We present UV, optical, and near-infrared (NIR) photometry of the first electromagnetic counterpart to a gravitational wave source from Advanced Laser Interferometer Gravitational-wave Observatory (LIGO)/Virgo, the binary neutron star merger GW170817. Our data set extends from the discovery of the optical counterpart at 0.47-18.5 days post-merger, and includes observations with the Dark Energy Camera (DECam), Gemini-South/ FLAMINGOS-2 (GS/F2), and the Hubble Space Telescope (HST). The spectral energy distribut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
581
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 840 publications
(646 citation statements)
references
References 62 publications
51
581
0
2
Order By: Relevance
“…Data taken on days 5.5, 6.5, and 11.5 were obtained in poor weather conditions, hence the broader uncertainty bands. The photometry has been checked against a difference imaging reduction using Pan-STARRS PS1 templates (Cowperthwaite et al 2017) and a galaxy fit and subtract PSF source magnitude reduction; these measurements are consistent with our results. The dashed lines show the initial decay of the source: µ a -m t , where a = ( ) 2.0, 1.4, 0.7, 0.5, 0.5, 0.4 in u, g, r, i, z, Y bands, respectively.…”
Section: Candidate Selectionsupporting
confidence: 72%
See 2 more Smart Citations
“…Data taken on days 5.5, 6.5, and 11.5 were obtained in poor weather conditions, hence the broader uncertainty bands. The photometry has been checked against a difference imaging reduction using Pan-STARRS PS1 templates (Cowperthwaite et al 2017) and a galaxy fit and subtract PSF source magnitude reduction; these measurements are consistent with our results. The dashed lines show the initial decay of the source: µ a -m t , where a = ( ) 2.0, 1.4, 0.7, 0.5, 0.5, 0.4 in u, g, r, i, z, Y bands, respectively.…”
Section: Candidate Selectionsupporting
confidence: 72%
“…Results agree within uncertainties and calibration differences. The photometry used in the next paper in this series (Cowperthwaite et al 2017), measured using a difference image reduction using Pan-STARRS PS1 templates, also agrees within uncertainties.…”
Section: Discovery and Observationsmentioning
confidence: 81%
See 1 more Smart Citation
“…This multimessenger data provided convincing answers to many outstanding questions. For instance, the detection of a short gamma ray burst (GRB) 1.7 seconds after GW170817 [24][25][26], and subsequent kilonova [27][28][29][30][31][36][37][38][39][40][41][42][43][44], confirmed that BNS mergers are a progenitor of these events. Lanthanide signatures in the kilonova light curves also showed BNS mergers to be a major site for nucleosynthesis of elements heavier than iron [40,44,47,48].…”
Section: Introductionmentioning
confidence: 78%
“…Taking our fiducial kilonova model, the current generation of wide-field telescopes, such as DECam [29], Pan-STARRS [39] and VISTA [40], which have limiting magnitudes around 22 would be able to observe kilonova emission to z ≈ 0.1 or a luminosity distance of 400 Mpc. The results in Figs.…”
Section: Implication For Em Follow-upmentioning
confidence: 99%